'To all my friends, known and unknown, close and distant': Or how to think about thinking about performance art1. (19th May 2021) - Rutgeerts, Jonas
Abstract : In 'To all my friends, known and unknown, close and distant': Or how to think about thinking about performance art, Jonas Rutgeerts advances 'friendship' as a method—a 'conceptual personage'—to understand the relation between the knowledge that is developed in and through performing arts practices and the thinking about performing arts, most often produced within the academic field. Building on the work of French philosopher Maurice Blanchot the author highlights the 'tacit' element that is at the heart of this relation. Blanchot defines friendship in terms of discretion, as a relation that can only exist through the recognition of an interval that, 'from me to this other who is a friend, measures all that is between us'. This interval prevents me from speaking about my friends, reducing them to a topic of conversation. According to Blanchot, we can only speak to our friends, acknowledging their irreducible otherness or strangeness. Similarly, thinking about the knowledge that is produced through performance should take on the form of a 'separation-relation', a relation that does not try to fuse dance and theory into one all-encompassing theory, but takes the fundamental alterity of both fields as a starting point for the creation of a singular and always changing dialogue.